2019
DOI: 10.1038/s41598-019-46714-7
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Performance of Multilayer Stents in the Treatment of Aneurysms with a Branch Attached

Abstract: Although multilayer stents (MSs) can be used to treat aneurysm effectively, for some aneurysms with branches attached, the hemodynamic mechanisms are still unclear. In this work, we modeled five cases that involve 1–4-layer stents implanted in aneurysms with side branches, and the numerical approach was used. Case 1 corresponds to an aneurysm without a stent, and cases 2–5 represent 1–4-layer stents being employed within aneurysms, respectively. The results showed that the velocity within the sac declined dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In one patient, we used a Leo intracranial stent, which is a nitinol self-expanding braided stent that is well suited for aneurysms on small tortuous arteries. Finally, stent grafts and flow diverters can be useful to preserve distal vascularization [ 16 , 17 , 18 , 19 ]. Initially, coronary stent grafts were used because of their high flexibility [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one patient, we used a Leo intracranial stent, which is a nitinol self-expanding braided stent that is well suited for aneurysms on small tortuous arteries. Finally, stent grafts and flow diverters can be useful to preserve distal vascularization [ 16 , 17 , 18 , 19 ]. Initially, coronary stent grafts were used because of their high flexibility [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the consistency of the data with a very high success rate and both recurrences successfully treated by endovascular techniques support this treatment method for patients with RAAs [ 52 ]. Few experimental in vitro and/or in vivo studies are reported regarding the use of numerical simulation and laboratory modelling to assess the different endovascular techniques available for the treatment of renal artery aneurysms [ 16 , 17 , 53 ]. Evaluation of functionality and biological response of those models would be of major interest and needs further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al observed a “special flow path” reserved inside the thrombosed aneurysm sac for the runoff of branches in such scenarios 16 . Other hemodynamic studies also demonstrated that the blood flow of collateral arteries was not compromised by the placement of FDS 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…It is capable of remodeling vessel walls, initiating a self-healing thrombus formation and thereby degenerating aneurysm as well as allowing blood flow through its mesh, so we can reach a good compromise between TAAAs repair and the maintenance of patency in visceral vessels. [7][8][9] It has been documented that MS has become a promising therapeutic alternative for the repair of complex TAAAs cases due to its low-cost, off-the-shelf nature, compared to a custom-made chimney, fenestrated or branched EVAR. [10][11][12] Recently, many studies have engaged in uncovering the potential role of MS in aneurysm treatment.…”
Section: Introductionmentioning
confidence: 99%